Amplified Circularly Polarized Electroluminescence Behavior Triggered by Helical Nanofibers from Chiral Co‐assembly Polymers. (5th April 2022) - Geng, Zhongxing; Zhang, Yuxia; Zhang, Yu; Quan, Yiwu; Cheng, Yixiang
Abstract: Two chiral binaphthyl polymers ( R / S ‐P1 and R / S ‐P2 ) with different dihedral angles of the binaphthyl moiety were chosen as chiral inducers to construct chiral co‐assemblies with an achiral pyrene‐naphthalimide dye (NPy ) and then acted as the emitting layer (EML) of circularly polarized electroluminescence (CP‐EL) devices. The anchored dihedral angle of R / S ‐P2 not only exhibited the enhanced chirality signal, but also had a strong chirality‐inducing effect on the achiral NPy dye in the chiral co‐assembly ( R / S ‐P2)0.6 ‐(NPy)0.4 . After annealing at 120 °C, the CPL signal (| g em |) of ordered helical nano‐fibers ( R / S ‐P2)0.6 ‐(NPy)0.4 was amplified to 5.6×10 −2, which was about 6‐fold larger than that of ( R / S ‐P1)0.6 ‐(NPy)0.4 . The amplified g em value of ( R / S ‐P2)0.6 ‐(NPy)0.4 was due to the formation of a helical co‐assembly through the strong π–π stacking interaction between the R / S ‐P2 and the achiral NPy . This kind of ordered helical nano‐fibers ( R / S ‐P2)0.6 ‐(NPy)0.4 acted as the EML of CP‐OLEDs, and achieved an excellent CP‐EL performance (| g EL |=4.8×10 −2 ). Abstract : The chirality and chiral induction ability of chiral binaphthyl‐based polymers can be regulated by changing the dihedral angle of chiral bi‐naphthyl moiety. The obtained circularly polarized organic light‐emitting diodes (CP‐OLEDs) based on the emitting layer (EML) of chiral co‐assembly ( R / S ‐P2)0.6 ‐(NPy)0.4 exhibit a high CP‐EL (electroluminescence) signal (| g EL |=4.8×10 −2 ) and an excellent device performance.